Pendampingan Usaha Kecil Pengrajin Batik Cirebon dalam Self-Assesment System Sesuai Peraturan Harmonisasi Peraturan Pajak pada Post Covid-19 Era - Widiastuti, Ni Putu Eka; Frederica, Diana; Magdalena, Febriani Cristina Susianti; Susilawati, Susilawati; Saprudin, Saprudin (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
Since the Covid-19 pandemic hit, business industries in Indonesia have struggled to revive their operations. The contribution of tax payments from Micro, Small, and Medium Enterprises (MSMEs) during the Covid-19 era has also declined. Out of a total of 64.2 million UMKM, only 2.3 million have a Taxpayer Identification Number and are actively paying taxes. In response to this situation, a community service initiative was undertaken by members of the Ikatan Akuntansi Indonesia, Department of Educator Accountants, DKI Jakarta, to assist MSMEs in the Batik Cirebon sector. The aim of this community service was to provide support to Batik Cirebon MSMEs in various areas, including planning, simple cash bookkeeping, determining production costs, sales of products, and introducing tax practices in the post Covid-19 era. The community service was executed through entrepreneur and e-commerce marketing training, tax compliance awareness sessions under the self-assessment tax system scheme for Batik MSMEs, and business consultations tailored for the Batik MSMEs. The outcome of this initiative showed an improved understanding among Batik Cirebon MSMEs in areas such as planning, cash bookkeeping, determining production costs, product sales, and tax practices after the Covid-19 pandemic. The results of this service are expected to be useful for improving the quality of governance towards improving the performance of Cirebon Batik MSMEs in the post-Covid-19 era.